Radiographic Evaluation of Medial Opening-Wedge High Tibial Osteotomy Using a New Internal Fixator with a Wedge-Shaped Spacer Block - Okimura, Shinichiro; Teramoto, Atsushi; Watanabe, Kota; Nuka, Satoshi; Kamiya, Tomoaki; Yamashita, Toshihiko (The Journal of Knee Surgery, 2020)
We developed a new internal fixator: a rigid T-shaped plate with locking screws and wedge-shaped spacer block for high tibial osteotomy. The purpose of the present study was to evaluate the radiographic outcome of opening-wedge high tibial osteotomy (OWHTO) using this new internal fixator. Sixty OWHTOs were performed in patients with medial compartment osteoarthritis and varus deformity (28 males and 23 females). Patients' mean age was 60.4 years. Preoperative and postoperative radiographs were obtained. The paired t-test was used to evaluate the differences over time with respect to radiographic variables. Union of the osteotomy gap was obtained in all patients, and no implant breakage was found. On anterior–posterior radiographs, a significant difference was observed (p < 0.01) between the preoperative and postoperative mean values of femorotibial angles (179.6 ± 3.2 vs. 170.6 ± 2.5 degrees), weight-bearing line ratios (23.8 ± 13.5 vs. 60.5 ± 11.5%), anatomical medial proximal tibial angles (84.8 ± 2.5 vs. 91.0 ± 2.6 degrees), and joint line coverage angles (3.6 ± 2.0 vs. 2.4 ± 1.7 degrees). On lateral radiographs, posterior tibial slopes were 11.5 ± 3.9 degrees preoperatively and 12.2 ± 4.0 degrees postoperatively (p < 0.01), and Insall–Salvati ratios were 1.04 ± 0.12 preoperatively and 1.06 ± 0.13 postoperatively (p = 0.24). Performing OWHTO using a new internal fixator with a wedge-shaped spacer achieves adequate correction of lower limb alignment without implant-related complications. This is a Level IV, case series study.
Keywords: internal fixator; medial opening-wedge high tibial osteotomy; osteoarthritis; implant failure